Macroalga Biodiversity at Karapyak Beach Pangandaran - Fini Hidayanti; Tati Kristianti; Leni Sri Mulyani (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Karapyak Beach Pangandaran is area coast potentially rocky and sandy​ support growth macroalgae. However, information about diversity macroalgae in this region Still limited. This research aimed  to observe types and distribution of macroalgae on Karapyak Beach, Pangandaran. Study done use method survey descriptive with technique line and quadrant transects measuring 1 m × 1 m. Determination station observation done by purposive sampling as many as three stations in the intertidal zone. Identification macroalgae done based on characteristics thallus morphology in general macroscopic, including shape, color, and structure body. Research result show that macroalgae found​ consists of on three main divisions, namely Chlorophyta, Phaeophyta, and Rhodophyta, with a total of ten type. Identified type​ including Sargassum sp., Sargassum polycystum, Padina australis, Chaetomorpha crassa, Boergesenia forbesii, Ulva lactuca, Eucheuma cottonii, Gelidium robustum, Palmaria palmata, and Amphiroa beauvoisii. Distribution macroalgae influenced by factors environment like type substrate, intensity light, and tidal conditions.Study This provide initial data about diversity macroalgae on Karapyak Beach which can utilized as base management and conservation ecosystem coast.